Pemberdayaan Komunitas Nelayan Kalibaru - Sugianto Sugianto (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The Community Service Program implemented in the Assisted Village in Kalibaru Village, Cilincing District, is designed with two strategic objectives. First, this program aims to foster creativity, motivation, and innovation among fishermen in optimizing marine potential and resources, which is realized through training and mentoring in marine business development. Second, this program also seeks to increase fishermen's awareness of the surrounding environmental conditions, by holding training on domestic waste management to create a sustainable and sustainable environment. To achieve these two objectives, this program applies a series of integrated methodological approaches, including Participatory Rural Appraisal (PRA) which emphasizes active community participation, Entrepreneurship Capacity Building (ECB) to strengthen the entrepreneurial spirit, Technology Transfer (TT) in the form of processing technology transfer, and the use of Information Technology (IT) to support information dissemination and marketing. All of these approaches are implemented through various forms of activities, such as counseling, practical training, and continuous intensive mentoring. The target of this program is the Kalibaru Fishermen's Group, which has 10 members, who were selected representatively to represent the fishing community in the Kalibaru area. The limited number of participants allowed for more intensive and targeted training and mentoring, and facilitated the individual evaluation and impact measurement of the program. Overall, the program yielded two main outcomes. First, there was a significant increase in participants' knowledge and skills, particularly in fishery product processing through training in making fish nuggets as a value-added diversification product. Second, the participating fishermen demonstrated improved capabilities in domestic waste management, which directly contributed to a cleaner and more sustainable coastal environment. The program implementation was evaluated using partner satisfaction indicators, measured through the distribution of survey instruments to all participants. The evaluation results showed that 97.5% of participants expressed satisfaction with all aspects of the program, while the remaining 2.5% expressed some satisfaction. This very high level of satisfaction indicates that the Community Service Program has successfully met the expectations and needs of the target community and can therefore be recommended for development and replication in other coastal areas.